Clinical Image-1: The great imitator Vol. 37(1) 2026 - Hoque, Mohammad Mahfuzul; Tasneem, Tahsina; Bari, Shafiqul (Bangladesh Journal of Medicine, 2026)
Abstract not available Bangladesh J Medicine 2026; 37(1): 80